Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
(x2-5x+1)2+2(5x-1)(x2-5x+1)+(5x-1)2
= [(x2-5x+1)+(5x-1)]2
= (x2-5x+1+5x-1)2
= (x2)2
= x4
A = (5\(x\) + 1)2 + (5\(x\) - 1)2 - 2.( 5\(x\) +1).(5\(x\) - 1) tại \(x\) = 1
Thay \(x\) = 1 vào A ta có:
A = (5.1 + 1)2 + (5.1 - 1)2 - 2.(5.1 + 1).(5.1 - 1)
A = 62 + 42 - 2.6.4
A = 36 + 16 - 48
A = 52 - 48
A = 4
a) \(\left(5x-2\right)\left(5x+2\right)-\left(5x+3\right)\left(5x-4\right)=0\)
\(\Leftrightarrow5x+8=8\)
\(\Leftrightarrow5x=8-8\)
\(\Leftrightarrow x=5.0\)
\(\Leftrightarrow x=0\)
b)
TÌM X biết:
a. (5x - 2)(5x + 2) - (5x + 3)(5x - 4) = 8
b. (4x - 3)( 4x + 2) + (4x + 5)(1 - 4x) =2.52
a ) \(\left(5x-2\right)\left(5x+2\right)-\left(5x+3\right)\left(5x-4\right)=8\)
\(\Leftrightarrow\left(5x\right)^2-4-\left(25x^2+15x-20x-12\right)=8\)
\(\Leftrightarrow25x^2-4-25x^2-15x+20x+12=8\)
\(\Leftrightarrow5x+8=8\)
\(\Leftrightarrow5x=0\)
\(\Leftrightarrow x=0\)
Vậy \(x=0\)
b ) \(\left(4x-3\right)\left(4x+2\right)+\left(4x+5\right)\left(1-4x\right)=2.5^2\)
\(\Leftrightarrow16x^2-12x+8x-6+4x+5-16x^2-20x=50\)
\(\Leftrightarrow-20x-1=50\)
\(\Leftrightarrow-20x=51\)
\(\Leftrightarrow x=-\dfrac{51}{20}\)
Vậy \(x=-\dfrac{51}{20}\)